PENGARUH PROMOSI DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MELALUI E-COMMERCE SHOPEE (STUDI PADA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PAMULANG) - Ahmad Syaflihuddin; Sugeng Widodo (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to examine the Influence of promotion and consumer trust on purchase decisions in Shopee E-Commerce (A Study on students of the management study program, Faculty of Economics and Business, Pamulang University), both partially and simultaneously. The sampling technique used random sampling to obtain a sample of 96 respondents in this study. The research findings indicate that promotions (X1) and consumer trust (X2) significantly influence purchase decisions, with a regression equation of Y = 2.501 + 0.543 (X1) + 0.620 (X2). The coefficient of correlation, indicating the strength of the relationship between the independent variables and the dependent variable, is 0.838, indicating a strong correlation. The coefficient of determination is 0.703, suggesting that promotions and cunsomer trust influence on purchase decisions in the amount of 70,3%, while the remaining 29,7% is influenced by other factors not examined in this study. The hypothesis test results show that the computed F value (110.019) exceeds the tabulated F value (3.094), and the p-value (0.000) is less than the significance level (0.05), leading to the rejection of the null hypothesis (H0) and acceptance of the alternate hypothesis (H3). This indicates a significant simultaneous effect of promotion and consumer trust on purchase decisions in Shopee E-Commerce (A Study on students of the management study program, Faculty of Economics and Business, Pamulang University).